Fern Flora of Uttarakashi District, Uttarakhand - Shah, Rakesh; Pande, H. C. (Indian Forester, 2010)
Uttarakhand constitutes a very significant and phyto-geographically important region in the world’s pteridophytic flora. In all 52 genera under 26 families, having l86 species, are being reported in the present communication.